1994
DOI: 10.1128/aem.60.5.1684-1686.1994
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Vibrio cholerae O139 synonym Bengal from the aquatic environment in Bangladesh: implications for disease transmission

Abstract: Currently, Bangladesh is experiencing an epidemic of acute watery diarrhea caused by Vibrio cholerae 0139. Surface waters were collected and cultured for vibrios following enrichment. Twelve percent (11 of 92) of samples yielded V. cholerae 0139, and all of them were positive for cholera toxin. The data suggest that V. cholerae 0139 is easily culturable from surface water samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…Serogroup O1 is less abundant in the intestine samples than non-O1 strains, and thus, its presence may have been masked by the non-O1 isolates, or the O1 strains may have entered the viable but non-culturable (VBNC) state [25]. V. cholerae O1 and O139 are rarely isolated from aquatic environments even in cholera-endemic areas like Kolkata and Bangladesh [25,26]. Senoh et al [27] suggested that this phenomenon can be explained by the fact that V. cholerae O1 and O139 enter the VBNC state.…”
Section: Discussionmentioning
confidence: 99%
“…Serogroup O1 is less abundant in the intestine samples than non-O1 strains, and thus, its presence may have been masked by the non-O1 isolates, or the O1 strains may have entered the viable but non-culturable (VBNC) state [25]. V. cholerae O1 and O139 are rarely isolated from aquatic environments even in cholera-endemic areas like Kolkata and Bangladesh [25,26]. Senoh et al [27] suggested that this phenomenon can be explained by the fact that V. cholerae O1 and O139 enter the VBNC state.…”
Section: Discussionmentioning
confidence: 99%
“…Some non-01 serogroup strains produce toxin and have caused sporadic cases of cholera and small outbreaks of diarrheal disease without causing widespread epidemics (1). The recently discovered serogroup 0139 is an exception, because it has caused epidemics in India (2) and Bangladesh (3).…”
mentioning
confidence: 99%
“…This organism continues to be a cause of epidemic and endemic cholera in the subcontinent and other parts of Asia (Bhattacharya et al 1993;Cholera Working Group 1993;Chongsa-Nguan et al 1993;Fisher-Hoch et al 1993). Studies have shown that this organism is likely to be a single clone, with all known strains having the same serotype and biochemical and toxin-producing properties (Islam et al 1994). In Tamil Nadu a resurgence of cases in July 1994 affected several towns including the one reported on here.…”
Section: Discussionmentioning
confidence: 78%
“…Since then, serotype 01 and 0 1 3 9 have both been isolated with similar frequency from sporadic cases. Islam et al (1994) have isolated this organism from surface waters of tanks, ponds and lakes. The organism has not previously been directly demonstrated in the drinking water supply.…”
Section: Introductionmentioning
confidence: 99%